Board profile and reporting timeliness: Evidence from Indonesia - Chantika Henny Renata Putri Hariyadi; Sri Murni; Nur Chayati; Arif Lukman Santoso (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study collects empirical information about the effect of Board of Directors characteristics—specifically board size, age, tenure, and meeting frequency—on the timeliness of financial reporting, indicated by Audit Report Delay (ARD). We utilize a purposive sample of 430 firm-year observations from consumer-cyclical companies listed on the Indonesia Stock Exchange from 2018 to 2022. We analyze data from multiple years, using agency theory to look at relationships while considering factors like profitability, auditor reputation (Big Four versus non-Big Four), and the effects of the COVID-19 pandemic. Research indicates that larger boards and increased meeting frequency correlate with reduced audit report delays, suggesting that structural board characteristics and active participation enhance supervision and accelerate report delivery. Conversely, the average age of directors and the tenure of board membership had no significant impact on the timeliness of reporting. The research elucidates the specific board characteristics that most significantly influence disclosure efficiency, thereby informing directors and investors about optimal governance procedures. These insights enhance corporate governance literature by differentiating the roles of structural and demographic board aspects in expediting disclosures. Regulators and corporations in emerging markets should prioritize appropriate board composition—specifically size and meeting frequency—to enhance reporting timeliness, transparency, and stakeholder confidence during unpredictable economic conditions.